Vaccine Innovation Conference 2017 - Vaccine Industry Committee (Frontiers Media S.A., 2017)
Proceedings from the Vaccine Innovation Conference 2017, held May 10, 2017, at Hyatt Regency Hotel, Montréal, QC, Canada, Presented by: Vaccine Industry Committee